2009
DOI: 10.1177/0022034509334100
|View full text |Cite
|
Sign up to set email alerts
|

Adult Rat Odontoblasts Lack Noxious Thermal Sensitivity

Abstract: Dentin hypersensitivity is a common symptom treated in the dental clinic, yet the underlying cellular and molecular mechanisms are not clear. We hypothesized that odontoblasts detect noxious thermal stimuli by expressing temperature-sensing molecules, and investigated whether temperature-activated TRP channels (thermo-TRP channels), which are known to initiate temperature signaling, mediate temperature sensing in odontoblasts. mRNA expression of dentin sialophosphoprotein and collagenase type 1, odontoblast-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 24 publications
4
29
1
Order By: Relevance
“…Similarly, in human odontoblasts differentiated in vitro from the pulp of extracted molar teeth, expression of TRPV1, TRPA1, and TRPM8 was described (El Karim et al, 2011). By contrast, odontoblasts isolated short term from adult rat incisors showed no evidence of TRPV1, TRPV2, TRPA1, and/ or TRPM8 expression (Yeon et al, 2009). To resolve these discrepant results, one might argue that either the actual odontoblasts are different from those obtained via in vitro differentiation or that the procedure of short-term isolation itself eliminates the odontoblasts that express TRPV1 or TRPV2.…”
Section: Transient Receptor Potential Channels: Acquired Diseasesmentioning
confidence: 97%
“…Similarly, in human odontoblasts differentiated in vitro from the pulp of extracted molar teeth, expression of TRPV1, TRPA1, and TRPM8 was described (El Karim et al, 2011). By contrast, odontoblasts isolated short term from adult rat incisors showed no evidence of TRPV1, TRPV2, TRPA1, and/ or TRPM8 expression (Yeon et al, 2009). To resolve these discrepant results, one might argue that either the actual odontoblasts are different from those obtained via in vitro differentiation or that the procedure of short-term isolation itself eliminates the odontoblasts that express TRPV1 or TRPV2.…”
Section: Transient Receptor Potential Channels: Acquired Diseasesmentioning
confidence: 97%
“…15 Briefly, upper and lower incisors were extracted within 5-10 min of sacrifice of the animal and were kept in cold (3-5 8C) Extracellular saline (ECS). After the surrounding soft tissues were all removed, the teeth were sectioned transversely with 500 mm thickness with a diamond disc for plaster.…”
Section: Preparation Of Odontoblastsmentioning
confidence: 99%
“…2,15 Briefly, the targeted cell was aspirated into a patch pipette with tip diameter of about 20 mm and put into reaction tube containing reverse transcription agents. Reverse transcription was for 1 h at 37 8C.…”
Section: Single-cell Reverse Transcription-polymerase Chain Reaction mentioning
confidence: 99%
See 1 more Smart Citation
“…Son et al used odontoblasts obtained by in vitro differentiation of pulpal cells of neonatal rats and found that odontoblasts expressed TRPV1, TRPV2, TRPV3, TRPV4, and TRPM3 by patch clamp recording and RT-PCR analysis [17]. Yeon et al used acutely isolated odontoblasts from adult rat incisors and reported that they could not find any evidence for the expression of TRPV1, TRPV2 by single cell RT-PCR, immunohistochemistry and functional analysis using calcium imaging [36]. Possible explanations for this discrepancy include: (1) the differentiated pulp cells might not be identical to the actual odontoblasts, (2) acutely isolation procedures damage the odontoblasts with TRPV1 or TRPV2, and (3) developmental difference in TRP expression between adult and neonatal rats.…”
Section: Thermo-trp Channels Expressed In Odontoblastsmentioning
confidence: 99%